Los antropónimos en los refranes meteorológicos de algunos pueblos eslavos. Sobre materiales de La sabiduría popular eslava en los refranes de F.L. Celakovsky - Pastyrik, svatopluk (Eslavística Complutense, 2004)
"Weather proverbs" result from a folk cognitive process based on the interaction of two pnnciples: the circle of nature and the calendar reflecting al1 saints and church holidays. The iatter became a foundation determining the knowledge of agriculture and climate and its passing onto the next generation. Since anthroponyms function in everyday communication they need not appear in their standardized forms. Anthroponyms in weather proverbs geathered in Celakovsky’s collection have provided good material for analysis and companson of Slavonic "weather proverbs".